Efeitos das propriedades mecânicas, tipos de ciclagem na tensão de contração e integridade marginal de diferentes selantes oclusais - Afonso, Ana Carolina Rezende (2020)
The purpose of this study was to evaluate the effect of mechanical properties of different materials used as sealant on stress shrinkage and integrity marginal and relation the results with two types of mechanical fatigue using Scanning Electron Microscopy (SEM) and Finite Element Analysis (FEA). The materials used in this study were a Resin-modified glass ionomer cement (RMGIC) Vitremer 3M, a Resin Sealant (RS) Prevent, FGM, and a Flow Resin (FR) (Filtek Bulk Fill Flow, 3M. The analyzed properties were Diametrical Tensile Strength (DTS), Compressive Strength (CS), Post-Gel Shrinkage (Shr), Knoop Hardness (KHN) and Elastic modulus (E). Shrinkage stresses were analyzed using FEA. Forty-five molars were sealed and divided into three groups of each material (N = 15), first group without mechanical fatigue (N=5), second group with mechanical fatigue with the conventional metallic tip (N=5), third group with mechanical fatigue simulating the bolus (N=5). Relating to the results obtained through SEM images and marginal integrity values. In DTS and CS RMGIC it presented values inferior to RS and FR. In Shr, RS and FR showed higher values when compared with RMGIC. RS showed greater KHN and E than other materials. At FEA, it was observed that RS had high retraction stresses in the region where the material was applied and mainly at the marginal interface. When RMGIC was subjected to mechanical cycling, it had the biggest failure in the enamel and material interface. The results obtained were correlated with the SEM images and integrity marginal values. All three materials are suitable considering all of their characteristics, but it is important to note that direct fatigue with the metal tip overestimates the failure values.